Latin American perspectives on sustainability in higher education - Rampasso, Izabela Simon; Anholon, Rosley; Quelhas, Osvaldo Luiz Goncalves; Velazquez, Luis; Mac-Lean Bravo, Claudia Alejandra (My University, 2023)
American perspectives on sustainability in higher educationLatin America presents several problems that demand debates and complex solutions.Many of these problems have historical roots, resulting from the formation process of these countries.However, these problems have worsened in the postpandemic scenario.The COVID-19 pandemic has destroyed social gains developed through years of improvement, causing millions of people to return to the poverty line (CEPAL, 2021;Gideon, 2020; UN, 2022).The region presents several problems that are directly addressed by the Sustainable Development Goals (SDGs) published by the United Nations (UN, 2015).The informality and deterioration of work (linked with the concerns related to decent work -SDG 8), poverty increasement (that is focused by SDG 1 and hinders the combat of hungry SDG 2) and the uncertainty regarding social programs continuity due to high levels of public debt became common concerns in almost all Latin American countries (directly affecting the SDGs 1, 2, 3, 4 and 8).And, as it is known, the above-mentioned problems are associated with an increase of violence against women (SDG 5), increasing inequalities (SDG 10) and deterioration of teaching conditions (SDG 4).The achievement of the SDGs, which already presented several challenges to be achieved, became even more difficult to be realized in the mentioned scenario as well as the ideals of sustainability based on a fairer society, with more egalitarian social services (UN, 2022).As highlighted by Zhao et al. (2022), besides making the existent barriers more complicated to be solved, the COVID-19 pandemic also created new challenges, reducing globalization and the connection between people.The Higher Education Institutions (HEIs), as centers of teaching, research and extension, have a very important role in this scenario, as they can evidence the most critical issues of Latin American society to be debated, propose solutions for them and, in special, prepare future professionals with a broader conception about their participation and responsibility in society (Sigahi et al., 2022;Sommier et al., 2022; UNESCO, 2017).Interesting initiatives are being developed by HEIs, and it is important to disseminate them to stimulate the development of other ones.Despite these initiatives, it is important to emphasize that Latin American HEIs have faced several problems, such as antiscience movements, brain drain, student learning gaps and mental health problems.And the COVID-19 pandemic scenario aggravated these challenges (Sigahi et al., 2022).Considering this context, this Special Issue aims to evidence important initiatives that are contributing to the sustainable development of Latin American countries.The articles published in this Special Issue assess students' learning experiences and concerns about sustainability, assess the impacts of HEIs on sustainability, assess the relationship between productive systems knowledge and sustainability in HEIs management, provide guidelines and examples for HEIs to develop sustainability related initiatives, among other contributions.We believe that all knowledge and experiences presented in this Special